2003
DOI: 10.1007/s10695-004-3321-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen consumption and feeding rates of gilthead sea bream (Sparus aurata) reveal lack of acclimation to cold

Abstract: Low temperature has been implicated in inducing outbreaks of 'winter syndrome' or 'winter disease' in farmed gilthead sea bream (Sparus aurata). The responses of gilthead sea bream to reduced temperature followed by maintenance at low temperature were studied. In a first experiment, oxygen consumption was measured when water temperature was reduced from 18 • C to 8 • C at either a rate of 1 • C · day −1 or as two 'sharp drops' (from 18 • C to 12 • C, and from 12 • C to 8 • C). In a second experiment, the water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
30
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 16 publications
(17 reference statements)
2
30
0
Order By: Relevance
“…As expected, MO 2 increased with temperature (Guinea & Fernandez 1997, Ibarz et al 2003, Libralato & Solidoro 2008. As temperature increases, biochemical reactions proceed faster (Angilletta et al 2002), and the metabolic cost of maintenance increases (Fry 1947(Fry , 1971.…”
Section: Effect Of Temperature On Rmr and Lossupporting
confidence: 66%
See 1 more Smart Citation
“…As expected, MO 2 increased with temperature (Guinea & Fernandez 1997, Ibarz et al 2003, Libralato & Solidoro 2008. As temperature increases, biochemical reactions proceed faster (Angilletta et al 2002), and the metabolic cost of maintenance increases (Fry 1947(Fry , 1971.…”
Section: Effect Of Temperature On Rmr and Lossupporting
confidence: 66%
“…The capacity for feeding and growth increases with temperature until the thermal optimum is reached, and decreases thereafter (reviewed by Fry 1947, 1971, Farrell 2009, Pörtner 2010. The low feed intake and RMR observed at 12°C is in line with suggestions by Ibarz et al (2003) that this temperature represents a lower limit for suitable temperatures in S. aurata aquaculture. The highest temperature used in the present study (20°C) can be expected to be close to the optimal temperature for growth.…”
Section: Effect Of Temperature On Rmr and Losmentioning
confidence: 57%
“…The reduction in food intake at low temperatures has also been observed under laboratory-controlled conditions. Tort et al (2004) reported that a gradual decrease in water temperature led to a reduction in the ration proposed by commercial diets (Petridis and Rogdakis 1996), while Ibarz et al (2003) showed that below 13°C sea bream stop feeding altogether. This reluctance to feed did not depend on the rate of temperature drop , and feeding did not recover during extended periods at constant low temperatures such as 20 days at 12°C or 35 days at 8°C (Ibarz et al 2007a, b).…”
Section: Effects Of Decreasing Temperaturementioning
confidence: 99%
“…Experiment 3: acute and chronic values correspond to 3-7 and 30-35 days of experimental conditions (fromIbarz et al 2007b) b Daily requirements were calculated as 1 mg of oxygen consumed corresponding to 13.6 Jouls in energy equivalents(Brafield and Salomon 1972) c Food intake ration corresponds to food supply during trials as % of body weight. At 11-12°C Tort et al (2004) reported low food intake whereasIbarz et al (2003) showed fasting. In fluctuating conditions at 16°C, food intake rose from 0.3 to 1% during warm-…”
mentioning
confidence: 99%
See 1 more Smart Citation